ANALYSIS OF THE CALCULATION METHODS OF THERMOELASTIC STRESSES IN THERMALLY MASSIVE STEEL SLUGS AT HEATING (ANALYTIC OVERVIEW) - P. E. Ratnikov (Литьë и металлургия)
Analytic overview of the methods of thermoelastic stresses in thermally massive steel slugs at heating is given.